2015
DOI: 10.1128/jcm.01630-15
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae with Non-Beta-Lactamase-Mediated Beta-Lactam Resistance: Easy To Find but Hard To Categorize

Abstract: Haemophilus influenzae is a major pathogen, and beta-lactams are first-line drugs. Resistance due to altered penicillin-binding protein 3 (rPBP3) is frequent, and susceptibility testing of such strains is challenging. A collection of 154 beta-lactamase-negative isolates with a large proportion of rPBP3 (67.5%) was used to evaluate and compare Etest (Haemophilus test medium [HTM]) and disk diffusion (EUCAST method) for categorization of susceptibility to aminopenicillins and cefuroxime, using MICs generated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Examples include the risk of creating an inoculum effect by use of too high concentration of inoculum (Gould, Heidecker, & LiPuma, ); the risk of overestimating the growth of the bacteria by extending the period of inoculation before interpretation (EUCAST & ESCMID, ; Matuschek, Brown, & Kahlmeter, ); and the risk of decreasing the antimicrobial concentration due to interactions between components in inappropriate media and the antimicrobial agent. For H. influenzae , it has been shown that the Etest generally overestimates MICs at lower ranges and underestimates MICs at higher range using broth microdilution as the gold standard (Skare et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the risk of creating an inoculum effect by use of too high concentration of inoculum (Gould, Heidecker, & LiPuma, ); the risk of overestimating the growth of the bacteria by extending the period of inoculation before interpretation (EUCAST & ESCMID, ; Matuschek, Brown, & Kahlmeter, ); and the risk of decreasing the antimicrobial concentration due to interactions between components in inappropriate media and the antimicrobial agent. For H. influenzae , it has been shown that the Etest generally overestimates MICs at lower ranges and underestimates MICs at higher range using broth microdilution as the gold standard (Skare et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of current breakpoints has been debated 11,26–28. The MIC of gBLNAR has been previously reported between 0.5 and 16 µg/mL,11,26,27 and the reduced reliability of gradient tests for H. influenzae sensitivity to aminopenicillins has been documented 29…”
Section: Discussionmentioning
confidence: 99%
“…Non-enzyme-mediated resistance occurs through mutations in penicillin-binding protein 3 (PBP3), with ftsI gene mutations identified as a cause of decreased β-lactam-binding affinity. This is termed β-lactamase-negative ampicillin resistance (BLNAR) 11. Disk diffusion and gradient tests are routinely used to evaluate the antibiotic sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently found group of amino acid substitutions belonged to group II (19/53; 35.8%), which was also observed in studies from other European countries (3, 14, 20, 21, 36). We could not detect strains of the group III, which harbours high-level PBP3 alterations (11, 35).…”
Section: Discussionmentioning
confidence: 68%
“…In recent years, alterations in PBP3 leading to decreased binding affinity of certain beta-lactam antibiotics have emerged as a prevalent resistance mechanism in H. influenzae (35). In this study, we investigated the mutations in the ftsI gene encoding for PBP3 within a collection of clinical isolates from two Swiss hospitals.…”
Section: Discussionmentioning
confidence: 99%